PENGARUH PERTUMBUHAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL DAN KEBIJAKAN DIVIDEN PADA KINERJA PERUSAHAAN - Armini, Ni Nyoman Ayu; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2015)
This research was conducted to determine the effect of company’s  growth, management ownership and dividend policy on the company performance. The population in this research are companies which listed in capital market and the number is not known or  called infinite population. Sampling method uses purposive sampling method and obtained 314 sample which satisfies the criteria with number of observations is  912. The company performance is measured by Tobin's Q ratio The method that used for hypothesis test is multiple regressions analysis. The results showed that the company’s growth and managerial ownership has no effect on the company performance. While the dividend policy has positive effect on company performance. The results of this study do not support the agency theory, but supports the bird in the hand theory that proposed by Gordon and Lintner.
Keywords: company’s growth, management ownership, dividend policy, Tobin’s Q